Profile of Peri-urban and Rural Dairy Farmers : A Comparative Analysis - Kamta Prasad Dwivedi , Arun Kumar and Prakash Singh (Indian Journal of Extension Education, 2014)
This study was conducted in Faizabad district of Uttar Pradesh to study the socio-economic profile of peri-urban and ruraldairy farmers with a sample of 120 dairy farmer (60 peri-urban + 60 rural) selected from eight villages selected throughprobability proportionate sampling technique on the basis of herd size. The study revealed that the majority of peri-urban(88.33%) and rural dairy farmers (75%) were literate with the dominancy of joint family system (68.33% in peri-urbanand 65% in rural). The majority of peri-urban dairy farmers (63.33%) and rural dairy farmers (56.66%) were found to bemedium size family i.e. 5-8 members; and possessed pucca house 65 per cent and 61.66 per cent, respectively. Themajority of both type of farmers (90% and 78.33%) reported agriculture as their main occupation. Amajority of the periurban dairy farmers (46.66%) was found to be having marginal land holding, while rural dairy farmers (33.33%) werefound in each marginal and large land holding categories. The annual income of majority of the peri-urban and rural dairyfarmers (45% and 40%) was found in the category of ` 60,001/- to 90,000/- and 30,000/-1 to 60,000/- respectively. Thedominant mass media information sources were observed to be radio followed by mobile and television. Majority of periurban dairy farmers (55%) and rural dairy farmers (73.33%) were observed to be in the medium category of materialpossession. The medium level of scientific orientation, achievement motivation, economic motivation and valueorientation were found among both type of respondents.